Errata to “On Competition to Join a Simple Queueing System Before the Facility Opens - anonymous (Management Science, 1985)
Errata to Bell, Colin. 1985. On competition to join a simple queueing system before the facility opens. Management Sci. 31 (3, March) 358–367.